2015
DOI: 10.1007/s11914-015-0255-2
|View full text |Cite
|
Sign up to set email alerts
|

Cx43 and Mechanotransduction in Bone

Abstract: Bone adaptation to changes in mechanical stimuli occurs by adjusting bone formation and resorption by osteoblasts and osteoclasts, to maintain optimal bone mass. Osteocytes coordinate the actions of these cells on the bone surface by sensing mechanical forces and producing cytokines that increase or prevent osteoblast and osteoclast differentiation and function. Channels formed by connexins (Cxs) and, in particular, Cx43 in osteoblasts and osteocytes are central part of this mechanism to control bone mass. Cx4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…On the other hand, epidermal host cells expressed Cx26, and the expression of Cx26 in the adjacent non-cancer tissues may be useful to identify patients with a high risk of metastasis. Cx43 is expressed in osteoblasts as gap junction channels (32), and B16 cells express Cx26 (31). Further studies are needed to define a cell surface molecule involved in cell-cell interaction between B16 melanoma and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, epidermal host cells expressed Cx26, and the expression of Cx26 in the adjacent non-cancer tissues may be useful to identify patients with a high risk of metastasis. Cx43 is expressed in osteoblasts as gap junction channels (32), and B16 cells express Cx26 (31). Further studies are needed to define a cell surface molecule involved in cell-cell interaction between B16 melanoma and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, other evidence suggests that inhibiting this communication can enhance bone formation during loading High-resolution 3D imaging of osteocyte anatomy and pathology and preserve it during unloading, which is reviewed by Lloyd and colleagues (2014). Recent studies have shown that the osteocyte gap junction channel Connexin 43 plays an integral role in bone mechanobiology and osteocyte viability (Plotkin et al, 2015;Riquelme et al, 2015;Xu et al, 2015). Primary cilia.…”
Section: Onandlcn At the Ultrastructural Levelmentioning
confidence: 99%
“…Recent studies have shown that the osteocyte gap junction channel Connexin 43 plays an integral role in bone mechanobiology and osteocyte viability (Plotkin et al, 2015;Riquelme et al, 2015;Xu et al, 2015). Primary cilia.…”
Section: Pm Goggin Et Almentioning
confidence: 99%
“…In vitro studies showed that Cx43 expression is required for the response of osteoblastic and osteocytic cells to mechanical stimulation [120]. Based on this finding, it was hypothesized that the response to mechanical loading is eliminated, or at least reduced, in the absence of Cx43 in osteoblasts and/or osteocytes.…”
Section: Connexins In Bonementioning
confidence: 99%
“…This primes osteoblastic cells to respond to mechanical signals by a yet to be identified mechanism. However, the detailed molecular pathway that mediates this inhibitory effect of Cx43 on bone formation induced by mechanical forces remains to be determined [120]. …”
Section: Connexins In Bonementioning
confidence: 99%